2013
DOI: 10.4028/www.scientific.net/kem.554-557.2054
|View full text |Cite
|
Sign up to set email alerts
|

3D Simulation of Laser Assisted Side Milling of Ti6Al4V Alloy Using Modified Johnson-Cook Material Model

Abstract: During machining of hard materials, one approach to reduce tool wear is using a laser beam to preheat the material in front of the cutting zone. In this study, a new concept of laser-assisted milling with spindle and tool integrated laser beam guiding has been tested. The laser beam is located at the cutting edge and moving synchronously with the cutter. In experiment, a reduction in the resulting process cutting forces and tool wear has been observed in comparison to milling without laser. A three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The main objective is to achieve thermal softening in the entire cutting region. It is understood from literature survey that the temperature of 250-300 • C in the cutting zone is desired for an optimal machining characteristics of Ti6Al4V [13]. Consequently, the range of laser parameters is selected to achieve temperature around 300 • C in the cutting zone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main objective is to achieve thermal softening in the entire cutting region. It is understood from literature survey that the temperature of 250-300 • C in the cutting zone is desired for an optimal machining characteristics of Ti6Al4V [13]. Consequently, the range of laser parameters is selected to achieve temperature around 300 • C in the cutting zone.…”
Section: Resultsmentioning
confidence: 99%
“…Ayed et al [12] performed a 2D simulation of laser-assisted orthogonal cutting of Ti-alloy based on FEM and found that a 4-55 % reduction in cutting forces by varying laser power and laser-tool gap. Further, Zamani et al [13] performed 3D simulation of laser-assisted side milling of Ti6Al4V and observed 25-60 % reduction in the cutting forces. Many researchers analyzed laser heating for difficult to machine alloys to achieve optimum heat-affected depth and width to improve their machinability.…”
Section: Introductionmentioning
confidence: 99%
“…DEFORM software is often used for 2D analysis of machining processes [5,6], but often also used for 3D simulation [7,8], or can be analyzed by special processes with advanced machining methods [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Zamini et al studied 3D simulation of laser assisted side milling of Ti6Al4V alloy using modified Johnson-cook material model. Effect of cutting velocity, laser power and tool wear on cutting force was studied with and without laser and found that are less than the milling without laser [3]. Shi et al studied numerical and experimental investigation of laser-assisted machining of Inconel 718.…”
Section: Introductionmentioning
confidence: 99%